The Nexus of Physical and Psychological Pain: Consequences for Mortality and Implications for Medical Sociology. (June 2022) - Peele, Morgan; Schnittker, Jason
Although physical pain lies at the intersection of biology and social conditions, a sociology of pain is still in its infancy. We seek to show how physical and psychological pain are jointly parts of a common expression of despair, particularly in relation to mortality. Using the 2002–2014 National Health Interview Survey Linked Mortality Files (N = 228, 098), we explore sociodemographic differences in the intersection of physical and psychological pain (referred to as the "pain–distress nexus") and its relationship to mortality among adults ages 25 to 64. Results from regression and event history models reveal that differences are large for the combination of the two, pointing to an overlooked aspect of health disparities. The combination of both high distress and high pain is most prevalent and most strongly predictive of mortality among socioeconomically disadvantaged, non-Hispanic whites. These patterns have several implications that medical sociology is well positioned to address.